CROSS-SECTORAL GOVERNANCE AND ECONOMIC LAW: STRENGTHENING NATIONAL DEVELOPMENT AND EQUITABLE WELFARE - Sapta Nur Fallah; Frida Nurrahma Masturi; Ady Setyo Nugroho (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
This study examines the role of cross-sectoral governance and economic law in strengthening national development and equitable welfare by integrating the banking, mining, and services sectors. Using a qualitative library research design, the study reviews recent peer-reviewed literature published between 2021 and 2026 from reputable academic databases, including Scopus, ScienceDirect, SpringerLink, Emerald Insight, and Taylor & Francis. The selected studies were analyzed using content analysis and thematic synthesis to identify patterns in regulatory coherence, institutional coordination, financial inclusion, mining governance, service accessibility, public accountability, and distributive justice. The findings show that fragmented sectoral regulations often lead to overlapping authority, policy inconsistency, weak implementation, environmental and social risks, and an unequal distribution of economic benefits. Banking regulation supports development when financial stability is combined with inclusive and responsible financing. Mining governance contributes to welfare when resource exploitation is linked to environmental protection, community participation, local development, and transparent benefit sharing. The service sector serves as the primary channel through which economic gains are translated into public services, employment opportunities, infrastructure, and regional development. The study proposes an integrated cross-sectoral economic governance framework consisting of regulatory coherence, interinstitutional coordination, responsible resource allocation, inclusive service delivery, and distributive accountability. It concludes that economic law should serve as a meta-governance mechanism to align sectoral policies with shared development goals. National development should therefore be evaluated not only through economic growth, investment, and production, but also through social inclusion, environmental sustainability, regional equality, service accessibility, and the fair distribution of development opportunities across society.